Changes in Vowel Articulation with Subthalamic Nucleus Deep Brain Stimulation in Dysarthric Speakers with Parkinson’s Disease - Vincent Martel Sauvageau; Joël Macoir; Mélanie Langlois; Michel Prud’Homme; Léo Cantin; Johanna-Pascale Roy (Parkinson's Disease)
Purpose. To investigate changes in vowel articulation with the electrical deep brain stimulation (DBS) of the subthalamic nucleus (STN) in dysarthric speakers with Parkinson’s disease (PD). Methods. Eight Quebec-French speakers diagnosed with idiopathic PD who had undergone STN DBS were evaluated ON-stimulation and OFF-stimulation (1 hour after DBS was turned off). Vowel articulation was compared ON-simulation versus OFF-stimulation using acoustic vowel space and formant centralization ratio, calculated with the first (F1) and second formant (F2) of the vowels /i/, /u/, and /a/. The impact of the preceding consonant context on articulation, which represents a measure of coarticulation, was also analyzed as a function of the stimulation state. Results. Maximum vowel articulation increased during ON-stimulation. Analyses also indicate that vowel articulation was modulated by the consonant context but this relationship did not change with STN DBS. Conclusions. Results suggest that STN DBS may improve articulation in dysarthric speakers with PD, in terms of range of movement. Optimization of the electrical parameters for each patient is important and may lead to improvement in speech fine motor control. However, the impact on overall speech intelligibility may still be small. Clinical considerations are discussed and new research avenues are suggested.